Digital Financial Management Systems and Transparency Outcomes: A Case Study of ARKAS Implementation in BOS Fund Administration - Mubarok Fatahillah; Husnul Hafidhoh (Sekolah Tinggi Agama Islam Kuningan, 2025)
Background: Transparency in the management of School Operational Assistance (BOS) funds is a critical issue in improving accountability and governance in educational institutions. The Indonesian government has introduced the School Activity Budget Plan Application (ARKAS) as a digital tool to support transparent and accountable financial management at the school level. Aims: This study aims to examine the effectiveness of the ARKAS application in enhancing transparency in the utilization of BOS funds at SMP Khas Kempek Cirebon. Methods: This research employed a quantitative approach. Data were collected through questionnaires, document analysis, and administrative records involving relevant school stakeholders. Statistical analyses were conducted, including validity and reliability tests, classical assumption testing, and simple linear regression to assess the relationship between ARKAS usage and BOS fund transparency. Result: The findings indicate that the implementation of ARKAS has a significant and positive effect on BOS fund transparency. The application facilitates systematic budgeting, accurate reporting, and improved access to financial information, thereby strengthening accountability and stakeholder trust. Conclusion: The ARKAS application plays an important role in improving transparency in BOS fund management. Integrating ARKAS into school financial systems is recommended to enhance governance practices. Future studies are encouraged to examine its long-term impacts and applicability in broader educational contexts